The Impact of Fraud-Themed Course On Students' Attitude to Fraud. Does Previous Studies and Background Matter? - Maria Vassiljev (Journal of Accounting and Management Information Systems (JAMIS), 2020)
Research Question: The main research question is "Has the fraud examination had any impact on accounting and audit students' attitudes to fraud?" Motivation: The problem of financial statement fraud is still actual. Accountants and auditors need a special education about fraud and ethical values to recognize a situation of fraud. To examine the influence of a correspondent course Nguyen et al. (2008) have examined students' ethical values before and after the course of business ethics, Rennie and Rudland (2003) have researched potential impact of course on students' attitude to academic misconduct. The novelty of the study is a questionnaire built on the basis of Fraud Triangle to find out students' attitude to factors of fraud. Idea: The main idea is to examine whether the course of fraud examination changes accounting and audit students' attitude to fraud? Also, the study tries to find out is there any difference in attitude to fraud conditioned by students' background? Data: 55 postgraduate students of TalTech School of Business and Governance and 70 participants in the professional training programme "Accountant-financial officer" have filled in questionnaires in academic years 2015/2016–2018/2019. Tools: A questionnaire is chosen as a research method. Student's t-test and one-way analysis of variance (one-way ANOVA) are used to answer all research questions. Findings: The course of fraud examination has a slight positive influence on students' perception of fraud. A surprising result was that students without degree in accounting were slightly more optimistic in their ethical attitude to fraud. Younger and less experienced students more than others consider it possible for fraud to be committed. Therefore the course on ethics and fraud should be integral part of continuous education of accounting professionals. Contribution: Researches on topic of how to measure a change of attitude or ethical values have been combined, Fraud Triangle is offered as a basis for questionnaire.
Keywords: A23; M41; M42; G41; 650; attitude to fraud; auditors and accountants; professional ethics; continuous education